Introduction of a mobile unit to enhance a modal shift for the transport of powdered building materials - L. E. Westerink-Duijzer (Journal of Shipping and Trade)
Abstract Inland waterway transport (IWT) is generally considered to be an environmentally friendly alternative to road transport and might also bring cost benefits. Nevertheless, the modal share of IWT remains limited, which is partly due to the necessary pre- and post-haulage to transport goods to and from the port. This paper presents an innovative concept aimed at reducing these operational barriers for the transport of powdered building materials. We introduce a mobile loading unit that can directly pump the product from the loading location into the vessel over a limited distance, thereby ending the need for pre-haulage with trucks. Our results show that the modal shift, enabled by the mobile loading unit, can result in cost reductions up to 30% and $$\hbox {CO}_2$$ CO 2 emissions can be halved.